Faktor-faktor yang Mempengaruhi Pemanfaatan Jamban Keluarga di Kecamatan Jatibarang Kabupaten Brebes - Laeli Apriyanti; Bagoes Widjanarko; Budi Laksono (Jurnal Promosi Kesehatan Indonesia, 2019)
Background: Based on Basic of Health Research in 2013, as many as 39-40 million people still defecated carelessly, including those who dumped their waste into the river. In Brebes Regency in 2017, the District Budget Fund has built 1298 latrines for poor families. But from the evaluation and preliminary studies reported that there are still many families that have not utilized the latrine to the fullest. This study aims to analyze the factors influence the utilization of family latrines in Jatibarang Subdistrict, Brebes Regency.Method: This study is an analytic observational design using a cross sectional approach to analyze the factors influence the use of family latrines. The sample of this study was selected purposively as many as 103 heads of households involved who met the inclusion criteria, namely families who received latrine program through the district budget funds from 3 villages in Jatibarang Subdistrict.Results: There is a significant relationship between knowledge, attitudes, defecation habits, and family support with the use of family latrines. There is no significant relationship between education level, family income, health worker support, community leaders support, availability of clean water, distance a place to defecate in addition to latrines on the use of family latrines. It is recommended that increasing knowledge and attitudes to respondents as well as supports from family were also needed in improving utilizing latrines.